Development of Authentic Assessment Instruments for Saintifical Learning in Tourism Vocational High Schools - Sugiyono Sugiyono; Badraningsih Lastariwati; Emy Budiastuti; A Yudianto (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
Teachers of Tourism Vocational High Schools in assessing students’ performance generally use an invalid written test. It does not measure what it was designed to measure. Measurement of performance should use authentic assessments. The objectives of this study were (1) identifying aspects required to develop an instrument, (2) developing authentic assessment instruments on scientific learning of Tourism Vocational High Schools, and (3) developing authentic rubrics of scientific learning. This study was Research and Development applying the 4D model consisting of Define, Design, Developed, and Disseminate. The first year study completed stages of Defining and Designing, while the second year completed stages of Developing and Disseminating. The results of the first year study were the prototype of the instruments and the rubric script. This study generated 3 instrument prototypes, namely attitude instrument (8 items), knowledge instrument (9 items), and skills instrument (18 items), along with the rubrics for each instrument. The three instruments qualify face validity with expert judgment, content validity with Aiken formula, construct validity with goodness-of-fit test, and reliability estimate with Intraclass Correlation Coefficient.